The Determinants of the Financial Performance of Insurance Companies in Mauritius - Appiah, Emelia (Department of Finance and Tax, 2020)
The study examines the effects of internal factors, made up of firm specific variables, and the external factors, consisting of industry and macroeconomic variables, on the financial performance of insurance companies in Mauritius. In particular, the study investigates the impact of firm size, leverage, gross written premiums, reinsurance, combined ratio, market concentration, foreign exchange, inflation and GDP growth on the profitability of insurers in both the life and the nonlife markets. Profitability was proxied by return on assets (ROA) and the underwriting profit ratio (UWPR). The study employs an unbalanced panel data sample of twenty non-life and seventeen life insurers from 2008 to 2016, with one hundred and twenty-two (122) non-life and ninety-eight (98) life firm-year panel observations obtained from the Financial Services Commission (FSC) of Mauritius. The models were estimated using the sandwich estimator by White, (1980) and Eicker, (1963) within pooled OLS, fixed and random effects panel estimation techniques. The findings show that, a unit increase in the combined ratio and leverage of life insurers impact negatively on the return on assets (ROA), while an increase in reinsurance dependence and firm size impact underwriting profit ratio positively. In the non-life sector, the findings show that insurance companies' profitability is positively impacted by increases in the combined ratio and gross written premium, while market concentration and foreign exchange negatively impacted non-life insurers' profitability. The findings of the study help us to understand firm pricing behaviour within the insurance industry and help to protect consumer interests in the pricing of policies. The findings also have implications on the growth strategies and risk management activities of insurance companies in Mauritius.